Fermentation of Formulated Feed using Bacillus subtilis TS2b for Giant Freshwater Prawn (Macrobrachium rosenbergii) Feed. Issue 1 (1st December 2022) - Mulyasari,; Samsudin, Reza; Subaryono,
Abstract: Giant prawn, Macrobrachium rosenbergii is a freshwater fishery product that requires further development. However, the high cost of commercial feed is one of the challenges in growing giant prawns. One approach to addressing this issue is to use local feedstuff as an alternative feed ingredient. The main obstacle to using local feedstuff is the limitation (anti-nutrition, crude fiber, etc.) that fermentation technology can overcome. The goal of this study was to create an efficient feed for giant prawns by fermenting formulated feed (which contains local feedstuff) using B. subtilis TS2b. Three treatments with three repetitions were used in this study with the following treatments: Treatment A consisted of commercial feed (as a positive control), Treatment B consisted of formulated feed (negative control), and Treatment C is a formulated feed that was fermented using Bacillus subtilis TS2b. The giant freshwater prawns used were 0.47±0.02g in weight and were randomly stocked into 9 aquarium units (60 × 50 × 45 cm) with a stocking density of 20 individuals/aquarium. Giant freshwater prawns were fed three times a day for 51 days of the rearing period. Absolute and relative weight growth, specific growth rate, survival rate, feed conversion, protein, and fat retention were all measured. The results showed that absolute growth for all treatments were : 1, 41±0, 22g (A), 1, 37±1, 37g (B), 1, 51±0, 04g (C), feed conversion were 1, 82% (A), 1, 83%(B), 1, 66%(C) and survival rate were: 72±2, 5%(A), 88±4, 7%(B) and 87±2, 4%(C).